China at the threshold of a market economy - Bell, Michael W.... [et al] (IMF WashingtonUS, 1993)
Reviews China's reform experience since 1978. Identifies special conditions that may have affected China's capacity to implement reforms and draws implications for the direction of China's future reform strategy.